Pre-service English Teachers’ Lived Experiences in Implementing Technology for Teaching Practice - Soepriyanti, Henny; Waluyo, Untung; Syahrial, Edy; Hoesni, Rizki Kurniawan (Technium Education and Humanities, 2022)
Since the emergence of the Covid 19 pandemic, the teaching practice conducted by the preservice English teachers in schools has experienced various changes. The Policy of Learning from Home (LFH) has urged these pre-service teachers to adopt and adapt the online learning technology that they never learn before. This situation has unduly created new challenges for those teachers. The present study aims to (a) to evaluate the perceived adequacy of the pre-service teachers’ technological knowledge and skills for teaching practices; (b) reveal their abilities to adapt to the demands of employing technology for the teaching practices; and (c) to bring to light challenges they faced in utilizing technology for teaching practice. The research employed a descriptive qualitative approach with a multiple case study design. The study involved 16 pre-service teachers doing teaching practices in the rural and urban schools. The results of the study show that the pre-service teachers participating in the two research sites had considerably divergent knowledge and skills in technology for learning. It was revealed from the study that students’ technological knowledge and skills was relatively low. Due to the absence of technological skills from their previous training and teaching practice preparation, on the average participants experienced difficulties in integrating technological knowledge and skills into their teaching-learning activities. The study concludes that professional development in the use of technology needs to be tailored into pre-service teachers’ preparation program prior to sending them to embark on teaching practices.